2006
DOI: 10.1016/j.devcel.2006.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Prospero Acts as a Binary Switch between Self-Renewal and Differentiation in Drosophila Neural Stem Cells

Abstract: Stem cells have the remarkable ability to give rise to both self-renewing and differentiating daughter cells. Drosophila neural stem cells segregate cell-fate determinants from the self-renewing cell to the differentiating daughter at each division. Here, we show that one such determinant, the homeodomain transcription factor Prospero, regulates the choice between stem cell self-renewal and differentiation. We have identified the in vivo targets of Prospero throughout the entire genome. We show that Prospero r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
460
0
14

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(491 citation statements)
references
References 71 publications
(84 reference statements)
17
460
0
14
Order By: Relevance
“…In one instance, Trbl suppresses a block in cell division caused by a dominant negative version of the Rho kinase Pebble (Gregory et al, 2007). As mentioned above, Trbl misexpression in male spermatagonia increases transit amplification of stem cells (Schulz et al, 2004); subsequently, it was shown that trbl RNA was down-regulated by the Prospero transcription factor, a negative regulator of spermatogonial stem cell proliferation (Choksi et al, 2006).…”
Section: -Present: Trbl Controls Cell Division During Tissue Pattmentioning
confidence: 96%
“…In one instance, Trbl suppresses a block in cell division caused by a dominant negative version of the Rho kinase Pebble (Gregory et al, 2007). As mentioned above, Trbl misexpression in male spermatagonia increases transit amplification of stem cells (Schulz et al, 2004); subsequently, it was shown that trbl RNA was down-regulated by the Prospero transcription factor, a negative regulator of spermatogonial stem cell proliferation (Choksi et al, 2006).…”
Section: -Present: Trbl Controls Cell Division During Tissue Pattmentioning
confidence: 96%
“…Once segregated to the GMC, Mira is degraded, thereby releasing Pros from the cortex (Ikeshima-Kataoka et al 1997;Shen et al 1997;Matsuzaki et al 1998). Pros can then enter the nucleus, where it has been thought to specify GMC identity by promoting the expression of GMC-specific genes and repressing the expression of neuroblast-specific genes (but see Choksi et al 2006).…”
Section: Neurogenesis In Drosophila (A) Neuroblast Formation: Notch Smentioning
confidence: 99%
“…In pins lgl double mutants, DaPKC is delocalized and inherited by both daughter cells, and thus neuroblasts undergo continuous symmetric self-renewing divisions (adapted from Lee et al 2006a). expression of Prospero in brat mutant clones rescues the brat phenotype (Bello et al 2006). Recently it has been shown, by whole genome mapping of the genes regulated by Prospero, that Prospero acts as a binary switch between stem cell self-renewal and differentiation, and that GMCs are transformed into neuroblasts in prospero mutant embryos (Choksi et al 2006). Brat is involved in the control of cell growth, possibly to maintain the size of neuroblasts as they undergo self-renewal.…”
Section: Neurogenesis In Drosophila (A) Neuroblast Formation: Notch Smentioning
confidence: 99%
“…4). Notably, mutations in genes that result in defects in function or asymmetric localization of cell fate determinants such as mutations in Pros, Numb, Brat or in their adaptors Mira and Pon result in massive tumorous overproliferation in the brain due to the production of supernumerary self-renewing daughters at the expense of differentiated cells (Bello et al, 2006;Betschinger et al, 2006;Choksi et al, 2006;Wang et al, 2006a). Neural tumors also result from mutation of other genes involved in asymmetric cell division such as discs large (dlg), lethal giant larva (lgl), and scribble (scrib) or the genes encoding the Aur-A and Polo kinases !…”
Section: ! 6!mentioning
confidence: 99%